Renal function in diabetes mellitus. Issue 4 (April 1985) - Davies, A G; Price, D A; Postlethwaite, R J; Addison, G M; Burn, J L; Fielding, B A
Abstract : Glomerular filtration rate, day and night-time albumin excretion, and blood pressure were estimated in 83 children with diabetes mellitus and compared with measures of glycaemic control, age, and duration of disease. Careful attention was paid to definition of normal values in age matched controls. The glomerular filtration rate was greater than normal, and correlated with duration of disease, but not with albumin excretion or blood pressure. Daytime albumin excretion correlated with duration of disease and glycosylated haemoglobin, but not with age, glomerular filtration rate, or blood pressure. Night-time albumin excretion was significantly raised and correlated with duration of disease, glycosylated haemoglobin, mean blood sugar concentration, and M value but not with age, glomerular filtration rate, or blood pressure. Diastolic blood pressure was significantly raised but was not correlated with any other measured variable. We have confirmed abnormalities of renal function in a children's diabetic clinic. The measurement of overnight albumin excretion rates may provide a sensitive early indicator of renal damage.